Speech-act theory to enhance Karl Barth's homiletical postulation of a sermon's revelatory compliance' - Thane, Markus -2015 (2015)
Karl Barth's theology is a theology which was born from the pulpit. For Barth the formulation and enactment of the unity of church, theology and proclamation had become an integral part of his life and theological legacy. While Barth taught as professor at the University of Bonn he published his first volume of his Church Dogmatics (CD) with an emphasis on divine revelation. At the time of the publication of CD I, Barth held two seminars on homiletics. The seminar notes were later assembled and turned into a book with the same title. If both works, CD I and Homiletics, are compared side by side a major theological inconsistency becomes apparent. In CD I Barth emphasises that revelation as the Word of God' remains with God, leaving the divine as the solely acting sovereign. Whereas in Homiletics, Barth talks about a sermon's Offenbarungsmässigkeit' - a sermon's revelatory compliance. These two postulations are not only in tension but they contradict each other. The underlying problem is that Barth cannot define revelation as a solely divine act which takes place separately and independently of human interaction; by simultaneously asking for a sermon and preachers' revelatory compliance, as if otherwise God would not be able to reveal himself. This poses the question as to how this inconsistency can be resolved. The underlying problem for Barth was at that time, apparently, upholding both divine revelation and human proclamation without compromising the character of God and the nature of a sermon. A way out of the dilemma can be found if revelation and sermon delivery are reframed and complemented by the philosophical approach of John R. Searle's and John L. Austin's speech-act theory'. Speech act theory' better appropriates Barth's desire to elevate a homily because of the reality change' which takes places in the very act of proclamation. In this theory proclamation is understood as a human act bound to God's truth which is creating a new reality' that opens and expects to have this reality filled and actualised by God's sovereign act of revelation. When proclamation/preaching is interpreted as speech-act theory', this follows Barth's desire to elevate the human act of the sermon delivery by simultaneously keeping the distinction between the human and divine, which is really worthy to be called a speech event.
Keywords: Karl Barth; Homiletics; Proclamation; Sermon; speech act